Mitochondria Dysfunction in Frontotemporal Dementia/Amyotrophic Lateral Sclerosis: Lessons From Drosophila Models - Anoar, Sharifah; Woodling, Nathaniel S.; Niccoli, Teresa (Frontiers in Neuroscience, 2021)
Frontotemporal Dementia (FTD) and Amyotrophic lateral sclerosis (ALS) are neurodegenerative disorders characterised by declining motor and cognitive functions. Even though these diseases present with distinct sets of symptoms, FTD and ALS are two extremes of the same disease spectrum, as they show considerable overlap in genetic, clinical and neuropathological features. Among these overlapping features, mitochondrial dysfunction is associated with both FTD and ALS. Recent studies have shown that cells derived from patients’ iPSCs display mitochondrial abnormalities, and similar abnormalities have been observed in a number of animal disease models. Drosophila models have been widely used to study FTD and ALS because of their rapid generation time and extensive set of genetic tools. A wide array of fly models have been developed to elucidate the molecular mechanisms of toxicity for mutations associated with FTD/ALS. Fly models have been often instrumental in understanding the role of disease associated mutations in mitochondria biology. In this review, we discuss how mutations associated with FTD/ALS disrupt mitochondrial function, and we review how the use of Drosophila models has been pivotal to our current knowledge in this field.